Study of the Anticancer and Antimicrobial Biological Activity of a New Series of Thiohydantoin Derivatives - Qusay Hussein Hays; Dakhil Zughayir Mutlaq (مجلة بغداد للعلوم, 2024)
Recently, some prostate cancer patients have acquired resistance to the second -generation drugs (anzalutamide and apalutamide) prescribed for the treatment of this disease due to the emergence of the F876L mutation, which represents a challenge to modern medicine. In this study, a new series of 2-thiohydantoin derivatives were prepared through the reaction of different derivatives of maleimide (1c-4c) with isothiocyanate derivatives. The prepared compounds were diagnosed using FT-IR,1H-NMR ,13C-NMR, Mass spectra. The prepared series compounds has been studied against prostate cancer cells. The MTT assay was used to determine the activity of the prepared compounds against prostate cancer cells. The data indicated, depending on the IC50 values, that some of the prepared compounds have anti-prostate cancer activity. The results indicate that compounds 1d and 2d have good anti-prostate cancer activity compared to the rest of the compounds. The prepared series of compounds were also studied against selected types of bacteria and fungi, as the results showed that some of the compounds in the series had anti-bacterial and anti-fungal activity.